The Effect Of Work Motivation And Managerial On Teacher Performance At SMP Negeri 1 Air Kumbang - Birahmatika, Dista; Fitria, Happy; Wahidy, Achmad (Jurnal Pendidikan Tambusai, 2021)
This research was conducted at the first high school 1 Air Kumbang, which is located at Jalan Impress Sidomulyo, Air Kumbang Sub-district, South Sumatra Province. explain whether there is a positive and significant influence of work motivation and managerial on teacher performance in junior high schools in Air Kumbang. This research is descriptive quantitative using a questionnaire and documentation. The results obtained in this study indicate that there is a very significant influence between work motivation on teacher performance and a very significant influence between managerial and teacher performance. Based on the research results, there are several suggestions given, namely: 1. The influence between variables is good and good. Thus, it is hoped that it can be maintained and even further enhanced by efforts to organize school principals. 2. by holding this research it is recommended that further researchers who will carry out research at school and by using the same variables, can do with a wider population using other research methods